Anti-discriminatory practice in counselling and psychotherapy - Lago, Colin; Smith, Barbara (London ; Thousand Oaks : SAGE, 2010)
Anti-discriminatory 'Practice in Counselling and Psychotherapy' is a ground-breaking text which identifies the ease with which individuals can be disadvantaged merely on the basis of their gender, race, culture, age, sexuality or ability.
1. Ethical Practice and Best Practice / Barbara Smith -- 2. Anti-Discriminatory Practice Revisited / Barbara Smith -- 3. Racism as a Trauma / Saira Bains -- 4. Child-Centred Practice / Camila Batmanghelidjh -- 5. Sexualities, Sexual Identities and Gender / Aaron Balick -- 6. Working with Women / Gillian Proctor -- 7. Disfigurement and Visible Difference / Suzy Henry -- 8. Therapy with Seriously Distressed Clients / Brendan Stone -- 9. Counselling, Psychotherapy and Religion / William West -- 10. Counselling Older People / Stephane Duckett -- 11. Working with Refugees / Jude Boyles -- 12. Class and Counselling / Anne Kearney -- 13. Therapy, Disability and Ethnicity / Zenobia Nadirshaw -- 14. Multiple Identities and Anti-Discriminatory Counselling Practice / Lee Murphy -- 15. Critical Thinking / Gail Simon.
Rev. ed. of: Anti-discriminatory counselling practice. 2003.
Keywords: Counseling; Discrimination; Psychotherapy; Prejudice; Ethnopsychology; Professional Practice; Professional-Patient Relations; Psychotherapy